Synthesis and biological evaluation of novel 3-(quinolin-4-ylamino)benzenesulfonamides as carbonic anhydrase isoforms I and II inhibitors - Mohammad M. Al-Sanea; Ahmed Elkamhawy; Sora Paik; Silvia Bua; So Ha Lee; Mohamed A. Abdelgawad; Eun Joo Roh; Wagdy M. Eldehna; Claudiu T. Supuran (Taylor & Francis Group, 2019)
Carbonic anhydrases (CAs, EC 4.2.1.1) are crucial metalloenzymes that are involved in diverse bioprocesses. We report the synthesis and biological evaluation of novel series of benzenesulfonamides incorporating un/substituted ethyl quinoline-3-carboxylate moieties. The newly synthesised compounds were in vitro evaluated as inhibitors of the cytosolic human (h) isoforms hCA I and II. Both isoforms hCA I and II were inhibited by the quinolines reported here in variable degrees: hCA I was inhibited with KIs in the range of 0.966-9.091 μM, whereas hCA II in the range of 0.083-3.594 μM. The primary 7-chloro-6-flouro substituted sulphfonamide derivative 6e (KI = 0.083 μM) proved to be the most active quinoline in inhibiting hCA II, whereas, its secondary sulfonamide analog failed to inhibit the hCA II up to 10 μM, confirming the crucial role of the primary sulphfonamide group, as a zinc-binding group for CA inhibitory activity.